PARAMETRIC MODELING OF BOLTED ASSEMBLY AND ITS COMPONENTS FOR INDUSTRIAL DESIGN AND APPLICATION - Bozherikov, Sylvester (Journal of Applied Engineering Science, 2026)
In the present work is proposed a methodology for parametric modeling of a bolted joint including four separate components, each of which is described with tabular dimensions according to current standard. The parametric model can automatically create a bolted assembly unit with a selected fastening size used for creating metal construction and bigger assemblies. Solutions are performed for the bolted joints used mostly in the industry.
Keywords: parametric modeling, bolt assembly, fastening size, tabular dimensions, design table